2012
DOI: 10.1007/s10904-011-9646-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesized of Sporopollenin-Immobilized Schiff Bases and Their Vanadium(IV) Sorption Studies

Abstract: This study investigated the potential use of a biologic polymer Lycopodium clavatum spores (Sporopollenin) for removal of vanadium ions (V(IV)) from aqueous solution. Three Schiff base derivative compounds immobilized sporopollenin were prepared and characterized. Immobilized sporopollenin was characterized via a scanning electron microscope, elemental analysis, infrared spectroscopy and thermal analysis techniques. The sorption capacities of the immobilized surfaces toward V(IV) ions were investigated by batc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…EDX spectrum corresponding to the inner red zone (i.e., inside the hollow capsule) is dominated by C and O signals without a signicant contribution from the Ti signal; conversely, the EDX spectrum for the outer blue zone (i.e., outermost surface) is dominated by Ti signals. These results are consistent with the thermogravimetric analysis (TGA) measurements in the literature, 29 which reported that while TiO 2 revealed a negligible gravimetric loss within 25-800 C, uncoated Lycopodium spores underwent almost 60% weight loss within 250-450 C due to thermal decomposition/degradation/oxidation processes.…”
Section: Resultssupporting
confidence: 91%
“…EDX spectrum corresponding to the inner red zone (i.e., inside the hollow capsule) is dominated by C and O signals without a signicant contribution from the Ti signal; conversely, the EDX spectrum for the outer blue zone (i.e., outermost surface) is dominated by Ti signals. These results are consistent with the thermogravimetric analysis (TGA) measurements in the literature, 29 which reported that while TiO 2 revealed a negligible gravimetric loss within 25-800 C, uncoated Lycopodium spores underwent almost 60% weight loss within 250-450 C due to thermal decomposition/degradation/oxidation processes.…”
Section: Resultssupporting
confidence: 91%
“…10 They have also been used for solid phase peptide synthesis, 11,12 as micro-reactors for the preparation of nanoparticles, 13 and as solid supports for palladium catalysed Heck reactions. 14 Functionalised SECs with either carboxylated or glyoximated diamino groups have been used for ion exchange and ligand exchange chromatography, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] often in conjunction with Co. 16,17,[19][20][21][24][25][26][27][28][29][30] The SECs have also been proposed for metal remediation and adsorption either on their own 31,32 or functionalised with carboxylate and glyoxime groups, 18,33 dithiocarbamates, 34 glutaraldehyde, 35 (E)-4-((2-hydroxyphenylimino) methyl) benzoic acid, 36 Schiff bases, [37][38][39][40][41] or calixarenes. 42,…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium, like other heavy metals, is widely distributed in the environment [70] and occurs naturally in variable concentrations in matrices such as soil and water [71]. When of natural origin, it is mainly a product of volcanic activity and soil erosion [72].…”
Section: Vanadiummentioning
confidence: 99%